Effectiveness of Telegram in English Language Learning among Technical Students in Derna, Libya. - Zainab Mumin,; Soad Issa,; Nuha Karaim, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study, guided by the Technology Acceptance Model (TAM), investigates the effectiveness of Telegram Messenger as a tool for English language learning among 38 third-year computer science students at the College of Technical Sciences in Derna, Libya. A structured questionnaire was used to explore students' perceptions of the app's usefulness, ease of use, and their behavioral intention to adopt it for learning purposes. The findings show that while Telegram positively influenced students' reading and writing skills, it had a lesser impact on their speaking and listening skills. Statistical analysis revealed a strong positive correlation between perceived usefulness and behavioral intention to use the app. However, a significant negative correlation was found between perceived ease of use and both usefulness and behavioral intention. The results suggest that Telegram can serve as an effective supplementary tool for English as a Foreign Language (EFL) learners, particularly when its use is enhanced with interactive content and activities that target all four language skills.